Preparation and Evaluation of Hot-Melt Extruded Patient-Centric Ketoprofen Mini-Tablets - S. Alshetaili, Abdullah; K. Almutairy, Bjad; V. Tiwari, Roshan; T. Morott, Joseph; M. Alshehri, Sultan; Feng, Xin; B. Alsulays, Bader; Park, Jun-Bom; Zhang, Feng; A. Repka, Michael (Current Drug Delivery, 2016)
Background: Bitter tasting drugs represent a large portion of active pharmaceutical ingredients. Mini-tablets are specifically designed for patients with difficulty in swallowing particular in young children up to 10 years of age, geriatric patients and patients with esophagitis. Objective: The present study was aimed to prepare, taste-masked mini-tablets, which are easily swallowed dosage forms, primarily to be used by pediatric and geriatric patients. Methods: Ketoprofen (10%-50% w/w) and Eudragit® EPO were blended and extruded with a 5-mm strand die and cut into consistent mini-tablets by using an adapted downstream pelletizer. Results: Differential scanning calorimetry and polarized light microscopy-hot stage microscopy studies confirmed that the binary mixtures were miscible under the employed extrusion temperatures. In-vitro release studies showed that drug release was less than 0.5% within the first 2 min in simulated salivary fluid (pH 6.8) and more than 90% in the first 20 min in gastric media (pH 1.0). The results of the electronic tongue analysis were well correlated with the drug release profile of the mini-tablets in the artificial saliva. Scanning electron microscopy revealed no cracks on the surface of the minitablets, confirming that the mini-tablets were compact solids. Chemical imaging confirmed the uniform distribution of ketoprofen inside the polymer matrices. Conclusion: Eudragit® EPO containing ketoprofen at various drug loads were successfully melt extruded into tastedmasked mini-tablets. The reduced drug release at salivary pH correlated well with Astree e-Tongue studies for taste masking efficiency.
Keywords: FTIR chemical imaging